The Importance of Location, Promotion, and Merchandising in Affecting the Consumer Purchasing Decision: A Case Study in PT Wijaya Motor Bandung, Indonesia - Dadang Suhairi (International Journal of Science and Society, 2020)
The purpose of this study was to determine the effect of location, promotion and merchandising on consumer purchasing decisions at PT Wijaya Motor Bandung, Indonesia. This research method uses a quantitative approach. The data collected in this study used the distribution of questionnaires to 118 consumers at PT Wijaya Motor Bandung using a simple random sampling technique. The results of this study indicate that there is a positive and significant effect both partially and simultaneously between location, promotion and merchandising on consumer purchasing decisions at PT Wijaya Motor Bandung, Indonesia.